At the intersection of ethnicity, gender, and sexual orientation: mental health status of ethnic minority youth in Aotearoa New Zealand - Naomi Simon-Kumar; Arier Lee; Shanthi Ameratunga; Roshini Peiris-John (Kōtuitui)
This study employed an intersectionality approach to examine mental health outcomes among ethnic minority youth in Aotearoa New Zealand. We analysed Youth’19 secondary school survey data and reviewed literature focusing on the experiences of ethnic minority youth who identify as female and/or sexual and gender minority (SGM). Our findings revealed significant disparities, with ethnic female and SGM youth reporting higher rates of poor wellbeing, depressive symptoms, and suicide attempts compared to their male and cisgender heterosexual counterparts. Experiences of racism intersect with sexism and cis-heterosexism to impact mental health outcomes for ethnic SGM youth, who face unique challenges due to cultural expectations, family relationships, and experiences of marginalisation in both ethnic and LGBTQI+ communities. While some protective factors like family support were identified in the literature, ethnic SGM youth struggle with internalised stigma, identity conflicts, and barriers to accessing culturally responsive mental health services. The findings highlight the importance of considering the multiplicity of marginalised identities that may be overlooked when focusing on single identity categories. Intersectional approaches provide an opportunity to gain a more nuanced understanding of the health status of New Zealand's ethnic minority populations, that goes beyond the healthy migrant effect.